PERAN SUPERVISI ARTISTIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SMA - Fitria Afrinawati; Dwi Fuji Hastuti; Sufyarma Marsidin; Rifma; Tia Ayu Ningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the role of artistic supervision in improving the pedagogical competence of junior high school teachers. This research was motivated by the suboptimal level of teachers’ pedagogical competence, particularly in lesson planning, classroom management, selection of teaching methods, and learning evaluation. This study employed a qualitative approach using a descriptive method, with data collected through observation, interviews, and documentation involving school principals, supervisors, and junior high school teachers. The results indicated that artistic supervision has been implemented through humanistic, dialogical, and reflective approaches; however, its implementation has not been optimal and consistent due to the continued use of traditional, instructional, and evaluative supervision approaches, as well as weak follow-up activities. This study concludes that artistic supervision plays an important role in improving teachers’ pedagogical competence, but it needs to be implemented systematically, collaboratively, and sustainably to achieve comprehensive and continuous improvement.